Proposta para implementação de startup como redução dos custos de transação na concessão e gestão do crédito rural pignoratício - Siqueira, Gabriela Porto (Universidade do Vale do Rio dos Sinos, 2023)
The global economic scenario, based on Transaction Cost Theory since 1937, is the basis for quantifying the value of goods and services in order to ensure favorable and efficient markets. By profiling governance structures for transactions, this work has highlighted the evolution of business by valuing positive economic performance for the parties and institutions. These guidelines, subject to the context of the financial system, make it possible to measure inventories, evaluate inputs and envision possible results linked to the production process, also in the agribusiness sector, based on the uncertainty generated by risk factors and the specificity of assets. With the solid evolution of the rural credit system in Brazil, current regulations demonstrate the incentives granted to farmers and rural producers through attractive subsidies. This stimulus, which fuels the contracting of credit lines, ends up generating a greater number of financial contributions and consequent investments in rural properties. Based on the expectation of growth in the total area planted in the country, there has been a profusion of technology in the agricultural sector, seeking productivity at a lower cost and greater safety. Within this context, rural inputs pledged as credit collateral are vulnerable to external and environmental adversities, generating defaults on obligations. This study sought to improve the packaging of goods, giving way to technological innovation optimized for an increasingly dynamic organizational environment. Using the Design Science Research methodology, we analyzed the various strategic visual tools that aim to refine business models, based on three main theories supported by specialists. Thus, the research gave rise to an applied case study, based on the development of a Canvas Business Model, synthesized from the proposal of a Startup in the Agtech segment, as an additional valve for reducing transaction costs in the granting and management of rural credit, in obligatory relationships between grantor and beneficiary. Through remote sensing and periodic analysis of the inputs used in agribusiness, the research looked at the contours of entrepreneurship linked to the law, establishing the appropriate value proposition based on the specific customer segment. The multifaceted study proved to be indispensable, and finally identified a complementary element to be considered in future projected models.
Keywords: Custos de transação; Crédito rural; Inovação; Modelo de negócios; Startup; Transaction costs; Rural credit; Innovation; Business model; ACCNPQ::Ciências Sociais Aplicadas::Direito